Center for the interpretation of cultural diversity in Jauja, Junín - Peru - Lebrún Aspillaga, Ana María (2016)
The Center for Interpretation of Cultural Diversity in Jauja is considered as an institution which promotes knowledge and dissemination of the historical and cultural legacy of Jauja’s provinces, where identity is consolidated with history, existing material and immaterial heritage, with the community participation of its inhabitants, to feel identified, promoting in this way the improvement within the social, cultural, economic and environmental areas in which it is inserted.Through the natural and cultural heritage in Jauja provides the necessary keys and tools to make understandable the patrimonial object and the context in which it appears, promoting the use and consumption of tourism products of the area in this space that will allow visitors expectations to know the territory and all that is in it. The general approach of the museography is based on providing different sensations and emotions to the visitor, as a space of communication, with elements of playful character, through an easy and comprehensible language, including a systematized work of teaching-learning  through formal, non-formal and informal education.